A complex role of Arabidopsis CDKD;3 in meiotic progression and cytokinesis. (6th March 2023) - Tanasa, Sorin; Shukla, Neha; Cairo, Albert; Ganji, Ranjani S.; Mikulková, Pavlina; Valuchova, Sona; Raxwal, Vivek K.; Capitao, Claudio; Schnittger, Arp; Zdráhal, Zbyněk; Riha, Karel
Abstract: Meiosis is a specialized cell division that halves the number of chromosomes in two consecutive rounds of chromosome segregation. In angiosperm plants is meiosis followed by mitotic divisions to form rudimentary haploid gametophytes. In Arabidopsis, termination of meiosis and transition to gametophytic development are governed by TDM1 and SMG7 that mediate inhibition of translation. Mutants deficient in this mechanism do not form tetrads but instead undergo multiple cycles of aberrant nuclear divisions that are likely caused by the failure to downregulate cyclin dependent kinases during meiotic exit. A suppressor screen to identify genes that contribute to meiotic exit uncovered a mutation in cyclin‐dependent kinase D;3 (CDKD;3) that alleviates meiotic defects in smg7 deficient plants. The CDKD;3 deficiency prevents aberrant meiotic divisions observed in smg7 mutants or delays their onset after initiation of cytokinesis, which permits formation of functional microspores. Although CDKD;3 acts as an activator of cyclin‐dependent kinase A;1 (CDKA;1), the main cyclin dependent kinase that regulates meiosis, cdkd;3 mutation appears to promote meiotic exit independently of CDKA;1. Furthermore, analysis of CDKD;3 interactome revealed enrichment for proteins implicated in cytokinesis, suggesting a more complex function of CDKD;3 in cell cycle regulation.